PENERAPAN MODEL PEMBELAJARAN LEARNING STATION UNTUK MENINGKATKAN MOTIVASI BELAJAR DALAM PEMBELAJARAN PJOK MATERI SENAM LANTAI PADA SEKOLAH DASAR - Rio Fahmi Praditya; Yusuf Hanafi; Anang Marzuqi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Low learning motivation in Physical Education, Sports, and Health (PJOK) classes remains a challenge in many elementary schools, particularly regarding floor gymnastics. This study aimed to enhance student motivation through the implementation of the